Social logistics as a mechanism for optimizing the management of the social sphere: theoretical and methodological aspect - Андрющенко, А. І.; Яковенко, Т. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
In the article within the limits of sociological approach conception of social logistic is offered as an universal mechanism of optimization of management a social sphere, specified it concept vehicle, system category which exposes essence of its object.